Strengthening Maritime Geopolitics Strategy to Counter Marine Resource Plundering in the North Natuna Sea - Apriani, Evi; Supriyadi, Asep Adang; Prakoso, Lukman Yudho; Widodo, Pujo; Suwarno, Panji (PT FORMOSA CENDEKIA GLOBAL, 2024)
The North Natuna Sea is one of the most strategic seas in Indonesia. However, the plundering of marine resources by countries nearby poses a serious threat to Indonesia’s maritime security. This article discusses the maritime geopolitical strategy to counter the looting of marine resources. In the North Natuna Sea. This research uses a qualitative approach using a literature study. The findings show the importance of maritime boundary analysis as the first step to tackle the looting marine resources, particularly through illegal fishing. Maritime patrol and surveillance, maritime cooperation and diplomacy, and raising maritime awareness as a strategy maritime geopolitics in countering the looting marine resources in the North Natuna Sea. In addition to that, strengthening the maritime economy also needs improved to realize prosperity the community from engaging in activities looting of these marine resources.